Phoneme production ability in stroke patients: A neuropsycholinguistic perspective - Darmayanti, Ida Ayu Made; Sutama, I Made; Sudiana, I Nyoman; Suandi, I Nengah; Rasna, I Wayan (Edelweiss Applied Science and Technology, 2025)
This study examines the ability to produce phonemes in stroke patients from a neuropsycholinguistic perspective. The case study involved two stroke survivors who experienced disturbances in the frontal lobe (located in the left hemisphere) and were categorized as having moderate strokes. Data were collected through in-depth interviews, audio recordings, and documentation. The analysis employed an interactive data analysis model, which included stages such as data condensation, data presentation, and conclusion drawing. The results indicated that speech production disorders in stroke patients are closely related to aphasia syndromes, particularly Broca’s aphasia, which causes articulation difficulties due to weakened motor control of speech organs. Patients were only able to produce limited sentences, typically consisting of four to six words. In addition to the consonant /r/, which is a phoneme with high complexity in tongue movement, there were also difficulties in pronouncing the consonants /s/, /l/, /t/, and /d/, which require coordination of tongue movement with the palate and teeth. Conversely, vowel phoneme production remained within normal limits. Consistent family support plays a significant role in accelerating speech recovery in patients. These findings contribute to a better understanding of post-stroke phonological disorders and can serve as a foundation for developing effective speech rehabilitation strategies.